House Movings and Alterations : Stability and Change in the Codroy Valley Landscape - Mackinnon, Richard (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1995)
By exploring house moving and alteration in the Codroy Valley, Newfoundland, this article focuses on how vernacular buildings change over time. It outlines the broad patterns of movings, additions and subtractions and provides some of the reasons for these activities.